2017
DOI: 10.1590/2317-1545v39n4177911
|View full text |Cite
|
Sign up to set email alerts
|

Controlled deterioration test and use of the Seed Vigor Imaging System (SVIS ® ) to evaluate the physiological potential of crambe seeds

Abstract: -Vigor tests are important tools for verifying the physiological potential of seed lots; however, various aspects can interfere in the consistency of the test results. The search for less subjective procedures has drawn the interest of researchers. The aim of this study was to adapt the methodology of the controlled deterioration test and verify the efficiency of the Seed Vigor Imaging System (SVIS ® ) to evaluate the vigor of crambe seeds. Initially, seed moisture content was determined and germination and vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 22 publications
0
15
0
4
Order By: Relevance
“…Santos and Rossetto (2013) found similar results using those same parameters for crambe seed lots differentiation of FMS Brilhante cultivar. In contrast, Leão-araújo et al (2017) observed the efficiency in seedling length tests made by computerized analysis system using Vigor-S® to detect differences in physiological quality of crambe seed lots.…”
Section: Resultsmentioning
confidence: 98%
“…Santos and Rossetto (2013) found similar results using those same parameters for crambe seed lots differentiation of FMS Brilhante cultivar. In contrast, Leão-araújo et al (2017) observed the efficiency in seedling length tests made by computerized analysis system using Vigor-S® to detect differences in physiological quality of crambe seed lots.…”
Section: Resultsmentioning
confidence: 98%
“…In the same manner, Silva et al (2012) concluded that seedling length and the vigor and growth indices obtained in analysis through the Seed Vigor Imaging System (SVIS®) were effective in classification of eggplant seed lots. Leão-Araújo et al (2017) indicated that the indices generated uisng SVIS®, including uniformity in seedling development, were able to effectively separate crambe seed lots.…”
Section: Resultsmentioning
confidence: 99%
“…This index is relevant since irregular seedling emergence can lead to delays in development and variations in growth of plants in various phenological stages, which also affects harvest results (Marcos-Filho, 2016). Leão-Araújo et al (2017) indicated that the indexes generated using the Seed Vigor Imaging System (SVIS ® ), including uniformity of seedling development, were able to separate crambe seed lots in an effective manner. Results obtained by Silva et al (2012) showed that uniformity of seedling development can provide useful information regarding the degree of seed deterioration, initial growth potential, and uniformity of seedling emergence of crotalaria.…”
Section: Resultsmentioning
confidence: 99%
“…possibility of using information from the indexes generated from development of seedlings to evaluate seed vigor (Leão-Araújo et al, 2017). The use of Vigor-S ® for computerized analysis of seedling images allowed the physiological potential of seeds to be evaluated through more than one parameter, which shows the possibility of taking better advantage of the results obtained from the same evaluation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation